2018
DOI: 10.1103/physrevlett.120.040404
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Time-Crystalline Order in Cavity and Circuit QED Systems

Abstract: Discrete time crystals are a recently proposed and experimentally observed out-of-equilibrium dynamical phase of Floquet systems, where the stroboscopic evolution of a local observable repeats itself at an integer multiple of the driving period. We address this issue in a driven-dissipative setup, focusing on the modulated open Dicke model, which can be implemented by cavity or circuit QED systems. In the thermodynamic limit, we employ semiclassical approaches and find rich dynamical phases on top of the discr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
215
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(220 citation statements)
references
References 94 publications
(158 reference statements)
3
215
0
Order By: Relevance
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The extension of DTC to open quantum system with drive and dissipation attracts widespread research interest recently. Concrete models [12,13] shown that the DTC order can exist in open system with appropriately engineered drive and dissipation. This prediction was confirmed by the authors of [12] who shown that the modified Dicke model with the help of sufficiently strong atom-photon coupling and photon loss can exhibit time crystalline structure, and the same prediction was reported in [13] that a dissipative Rydberg model is also possible to possess time crystal order.…”
Section: Introductionmentioning
confidence: 99%
“…For DTCs in open systems, there exist some physical observableÔ with expectation value O(t), and ( ) ( ) = + O t O t nT shows sub-harmonic response to the driving field of period T. Here n is an integer and n2. The Dicke model exhibits a zero-temperature phase transition from a normal to a super-radiant phase [12,14] when the light-matter interaction increase. The parity symmetry of the Dicke model is spontaneously broken in the super-radiant phase [12,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations